1991
DOI: 10.1002/1097-0142(19910401)67:7<1971::aid-cncr2820670725>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell adenocarcinoma of the vagina and cervix. A report of the central netherlands registry with emphasis on early detection and prognosis

Abstract: The Central Netherlands Registry (CNR) of women with vaginal or cervical clear cell adenocarcinoma (CCAC) was established in 1985. An overview is presented of clinical and pathologic data of 55 patients who were registered at the CNR until July 1, 1988. All Netherlands Departments of Pathology (NDP) maintain a patient registry and 95% of the Institutes are connected with a Central Archive via a computer network. The histologic slides and clinical status were reviewed at the CNR. Twenty-five tumors were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 11 publications
4
76
1
Order By: Relevance
“…The young age group is largely composed of woman exposed to diethylstilbestrol, whereas the latter is constituted mostly by those without history of exposure. 6 Several studies showed better prognosis in diethylstilbestrol induced carcinoma than those with spontaneous clear cell carcinoma. 7,8 The treatment of clear cell carcinoma is similar to that of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The young age group is largely composed of woman exposed to diethylstilbestrol, whereas the latter is constituted mostly by those without history of exposure. 6 Several studies showed better prognosis in diethylstilbestrol induced carcinoma than those with spontaneous clear cell carcinoma. 7,8 The treatment of clear cell carcinoma is similar to that of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The first peak occurs in women who are 17 to 37 years of age (mean age 26 years), and the second peak occurs in women who are 44 to 88 years of age (mean age 71 years). The former group includes most of DESexposed women, and the latter is constituted mostly by those without a history of DES exposure [3]. DES has been considered as a teratogen which crosses placental barrier [4].…”
Section: Discussionmentioning
confidence: 99%
“…Most women had early stage (stage I-II) disease and our patient was stage IIA. In a Dutch series of 88 women, 76 (88.5%) had stage I-II disease [3]. The primary treatment of early disease usually involved radical surgery with pelvic±para-aortic lymphadenectomy, with outcomes comparable to other types of cervical adenocarcinoma [14,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cytology showed clusters of adenocarcinoma cells of unequal sizes in which the nuclear/cytoplasmic ratio was high ( Figure 1 and Table 1). Sheet-like arrangements of cervical CCAC has been advocated in various publications [10], and doubts about its diagnostic value have also been expressed. One study found that 25% of cases of CCAC presented with false-negative smears [11].…”
Section: Cytological Findingsmentioning
confidence: 99%